Prediction of Body Weight from Linear Body Measurements in Nili-Ravi Buffalo Calves - Paul, Shyam Sundar; Das, Kalyan Sundar (Journal of Buffalo Science, 2012)
Using 24 Nili-Ravi male buffalo calves, an experiment was carried out to find out the correlation of body weight with linear body measurements and to test the accuracy and precision of regression equations to estimate body weight from linear body measurements. All the linear body measurements during 6 - 24 months of age were positively and significantly correlated with body weight (P< 0.01). The coefficient values were decreased gradually with the increase of age of calves. The body weight of 6-12, 12-18 and 18-24 month calves can be predicted on the basis of linear body measurements with very low standard error of estimates and the developed models explained 83.21, 82.23 and 66.66% of variation in body weight, respectively.